Brazilian Adults Believe that Complete Dentures would be the Solution to the Oral Impacts Caused by Reduced Dentition - Fernanda Lamounier Campos; Ichiro Kawachi; Gabriela Aparecida Caldeira Rhodes; Aline Araujo Sampaio; Loliza Luiz Figueiredo Houri Chalub; Raquel Conceição Ferreira (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the direct and oral impact-mediated association between reduced dentitions and the self-perceived need for complete dentures (CD) in dentate adults. Material and Methods: Data from the Brazilian Oral Health Survey (2010) were analyzed. The outcome was self-perceived need for CD. Functional dentition (FDClassV) was defined by the presence of the following criteria: level I - ≥1 tooth in each arch, level II - 10 teeth in each arch, level III - 12 anterior teeth, level IV - ≥ 3 posterior occluding pairs (POPs) of premolars and level V - ≥1 bilateral POPs of molars. Oral impacts were assessed with Oral Impacts on Daily Performances scale. Results: FDClassV was associated with a less self-perceived need for CD both directly and mediated by oral impacts. Dentitions without level V were associated with the outcome mediated by oral impacts. Between individuals with 10 teeth in each arch, self-perceived need for CD was similar for those who had or not anterior teeth and POPs. Individuals with <10 teeth in each arch and level III did not have a higher frequency of self-perceived need for CD compared to those with level II. Conclusion: Oral impacts mediated the association between reduced dentitions and self-perceived need for CD. Individuals with tooth loss may report need for CD, even when they have dental configurations compatible with functionality.